2019
DOI: 10.1002/chem.201904241
|View full text |Cite
|
Sign up to set email alerts
|

Amphoteric Homotropic Allosteric Association between a Hexakis‐Urea Receptor and Dihydrogen Phosphate

Abstract: Conformationally flexible hexakis-urea 1 was synthesized efficiently by condensing hexakis(aminomethyl)benzene with 4-nitrophenyl-(3,5-di-tert-butylphenyl)carbamate. The hexakis-urea 1 is unexpectedly soluble in organic solvents of low polarity duet oi ntramolecular hydrogen bonding. The hexakis-urea 1 recognizes chloride, bromide, and acetate in a1 :2 host-guest ratio and in a positive allosteric manner in CDCl 3 .T he ability of 1 to recognize dihydrogen phosphate is au nique outcome, and the structure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Urea derivatives with ethyl ( U‐C 2 ), propyl ( U‐C 3 ), butyl ( U‐C 4 ), pentyl ( U‐C 5 ), hexyl ( U‐C 6 ), heptyl ( U‐C 7 ), octyl ( U‐C 8 ), dodecyl ( U‐C 12 ), tetradecyl ( U‐C 14 ), pentadecyl ( U‐C 15 ), hexadecyl ( U‐C 16 ), and octadecyl ( U‐C 18 ) groups were synthesized by this method in 65–91% yields (Scheme 1). When an appropriate isocyanate was not commercially available, the desired urea derivative was synthesized by the following two steps: First, a carbamate was synthesized in 91% yield by the reaction of 2‐benzylaniline and 4‐nitrophenyl chloroformate [28] . The desired urea derivatives were then obtained by the reaction of this carbamate with alkylamines having the appropriate alkyl chains in the presence of Et 3 N as a base.…”
Section: Resultsmentioning
confidence: 99%
“…Urea derivatives with ethyl ( U‐C 2 ), propyl ( U‐C 3 ), butyl ( U‐C 4 ), pentyl ( U‐C 5 ), hexyl ( U‐C 6 ), heptyl ( U‐C 7 ), octyl ( U‐C 8 ), dodecyl ( U‐C 12 ), tetradecyl ( U‐C 14 ), pentadecyl ( U‐C 15 ), hexadecyl ( U‐C 16 ), and octadecyl ( U‐C 18 ) groups were synthesized by this method in 65–91% yields (Scheme 1). When an appropriate isocyanate was not commercially available, the desired urea derivative was synthesized by the following two steps: First, a carbamate was synthesized in 91% yield by the reaction of 2‐benzylaniline and 4‐nitrophenyl chloroformate [28] . The desired urea derivatives were then obtained by the reaction of this carbamate with alkylamines having the appropriate alkyl chains in the presence of Et 3 N as a base.…”
Section: Resultsmentioning
confidence: 99%
“…permit an even more effective and selective binding of anions? In line with the proposition, Mislow and co-workers found that the aaaaaa conformer of hexasubstituted benzene is the least stable and more than 8 kcal/mol above the ababab form. To overcome the bias from steric gearing, Allen and co-workers employed six primary amides to form a seam of intramolecular N–H···OC hydrogen bonds (HBs) around the benzene core for stabilizing its aaaaaa conformation . Moreover, Ghosh and co-workers discovered that the corresponding hexa-amide receptors would overcome the steric gearing by assuming conformations ( aaaaaa , aaabbb , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…132 To date, scientists have successfully developed numerous probes with hydrogen bonding-induced high-order structures, finding applications in acid-base recognition materials, temperature sensing materials, biological imaging, biological recognition, and mechanical sensing. 133 Benefiting from the hydrogen bonding-induced highly ordered supermolecule, the rapid development of high-resolution oxygen biosensors has occurred. Oxygen plays a crucial role in numerous physiological activities in the human body, 134 and its deficiency is associated with many diseases.…”
Section: Hydrogen Bondingmentioning
confidence: 99%